Volatility Spillovers in Electricity Markets: Evidence from the United States - Pantos, Themistoclis; Polyzos, Stathis; Armenatzoglou, Aggelos; Kampouris, Ilias (International Journal of Energy Economics and Policy, 2019)
This paper examines the degree of market integration, as observed by measuring volatility spillovers, in selected wholesale electricity spot markets from United States. We choose markets located at interconnected and non-interconnected areas. We use a Multivariate GARCH framework, which allows us to model time varying correlations and to conclude whether the markets show evidence of interdependency. We estimate the variance-covariance and correlation structure, in order to observe the evolution of interactions among markets, accounting for asymmetric effects. We find evidence of significant correlations between interconnected markets, which are mainly due to electricity transmission, since the observed correlations are above 0.5, but our results show that the desired level of integration has not been accomplished yet. Nevertheless, full integration is not an objective target, unless new technologies offer a boost towards that direction. Our results suggest that we should move towards a more integrated market, through legislation reforms and investment in infrastructure, which could increase competition and could lead to capital savings through lower electricity prices. The unique selection of the markets under examination and the 4-variate BEKK model for electricity markets are special characteristics of this paper. Keywords: Energy Markets, Electricity Markets, Market Integration, BEKK, Asymmetric Dynamic Conditional Correlation JEL Claasifications: Q43, Q48, O21, C44 DOI: https://doi.org/10.32479/ijeep.7563